The Influence of Marital Quality and Coping Strategy on Parenting Environment Quality in Long Distance Marriage Families - Syafhil, Jihan Fairuz; Herawati, Tin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Long distance marriage presents challenges and changes to family life both in terms of the quality of the marriage and the quality of parenting. This research aims to analyze the influence of marital quality and coping strategies on the quality of parenting in long distance marriage families. The approach in this research is quantitative with a cross-sectional study design. This study involved families undergoing long distance marriages with the criteria of a minimum separation of one month, having preschool aged children (3-6 years), and domiciled in Bogor Regency or City. The respondents in this study were 30 mothers. Sampling in this study used non-probability sampling with snowball sampling technique. The results study shows that the quality of marriage and the quality of the parenting environment are moderate, while coping strategies are classified as low. The results of the regression test show that the length of separation has a significant negative effect, while problem-focused coping and the child's gender have a significant positive effect on the quality of the parenting environment. There was no relationship or influence of marital quality on the quality of the parenting environment in this study. This research can be a basis for developing special support programs for long distance marriage couples as well as further knowledge in the context of long distance marriage.